STRATEGI OBYEK WISATA DI GUNUNG KIDUL - Lukia Zuraida; Marliana Handayani; Dwi Novitasari (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
Gunung Kidul District is one of areas in Yogyakarta Special Region in which has potentialities of special interests of natural tourist destinations. It has about 58 caves, 69 beaches, and many other natural tourist destinations. Most of them are Karst as the main potential of natural destinations. Regarding with the special interests on tourism, Gunung Kidul District has given contribution to the Yogyakarta Regional Revenue on tourism it’s about 4,5 billion in 2012. It means that there is increasing of the revenues about 133 % from 2011, with the regional revenue is about 1,7 billion. Based on the contributions of regional revenues on tourism field, and the significant increase of the tourists, especially in Pindul Cave and Indrayanti Beach during last five years, it is necessary to have research on Marketing Strategies of Pindul cave Tourist Destinations and Indrayanti Beach. The aim of the research is to analyze the Marketing strategy of Pindul cave and Indrayanti Beach. Another purpose to discover factors weather internal or external factors give influences to the Marketing strategy of Pindul Cave and Indrayanti Beach. To get comprehensive data, this research used several data collection methods, participary observations, and in–depth interview with visitors, agencies, communities, government, and local people. Based on the descriptive analyze of the 30 interviewers about Pindul Cave and Indrayanti Beach , most of them explained that marketing of Pindul Cave and Indrayanti Beach are quite good. The analyze proved that the agencies and the marketing strategies of Pindul Cave and Indrayanti Beach are at the first (I) quadrant (the Growth), in which they have opportunities and strengths to be developed, with the differencies of their opportunities and strength .